High-level activity and access to sport following lower limb amputation due to malignant musculoskeletal tumors versus trauma: a prospective comparative study - Schenker, Astrid; Wolf, Sebastian Immanuel; Alimusaj, Merkur; Putz, Cornelia; Lehner, Burkhard; Block, Julia (Archives of orthopaedic and trauma surgery, 2025)
Patients with musculoskeletal tumors who undergo amputation show reduced physical function. To give these patients better expectations of their future physical capabilities and to enhance the evaluation and development of postoperative rehabilitation, we investigated high-level activity and access to sport using objective measurements and questionnaires. We then compared the results to those of amputees who had undergone amputation due to trauma.